Genetically encoded fluorescent thermosensors visualize subcellular thermoregulation in living cells - Kiyonaka, Shigeki; Kajimoto, Taketoshi; Sakaguchi, Reiko; Shinmi, Daisuke; Omatsu-Kanbe, Mariko; Matsuura, Hiroshi; Imamura, Hiromi; Yoshizaki, Takenao; Hamachi, Itaru; Morii, Takashi; Mori, Yasuo (Nature methods, 2013)
Genetically encoded sensors based on GFP enable the visualization of subcellular thermal changes noninvasively in intact cells. In mammals and birds, thermoregulation to conserve body temperature is vital to life. Multiple mechanisms of thermogeneration have been proposed, localized in different subcellular organelles. However, visualizing thermogenesis directly in intact organelles has been challenging. Here we have developed genetically encoded, GFP-based thermosensors (tsGFPs) that enable visualization of thermogenesis in discrete organelles in living cells. In tsGFPs, a tandem formation of coiled-coil structures of the Salmonella thermosensing protein TlpA transmits conformational changes to GFP to convert temperature changes into visible and quantifiable fluorescence changes. Specific targeting of tsGFPs enables visualization of thermogenesis in the mitochondria of brown adipocytes and the endoplasmic reticulum of myotubes. In HeLa cells, tsGFP targeted to mitochondria reveals heterogeneity in thermogenesis that correlates with the electrochemical gradient. Thus, tsGFPs are powerful tools to noninvasively assess thermogenesis in living cells.